Se déplacer à la marge ? Première approche des mobilités des usagers de nouveaux espaces de travail collaboratif hors des métropoles - Benoit Feildel (Netcom)
The increased interest in coworking spaces on the margins of metropolitan areas invites us to question the supposed positive externalities of these places, which are widely acclaimed by public authorities, especially for their contribution to the transition to more sustainable mobility in a territorial system rebalenced on sparse areas. Mobility in these obviously low-density areas, located in discontinuity with urban areas and largely dependent on cars, is a major challenge for the ecological and social transition. By using two complementary survey tools, an online questionnaire and a GPS surveys, we question in a mainly exploratory aim the mobilities of coworkers on the margin of metropolitan areas. This first approach allows us to reveal the effect of territorial belonging and embeddedness in social relations on the structure of their users mobilities, and thus to glimpse a certain number of challenges and prospects for a transition towards a more sustainable ways of living in low density areas.